Impact of service station networks on purchase decisions of alternative-fuel vehicles - Martin Achtnicht; Georg Bühler; Claudia Hermeling (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
In this paper, we study the impact of fuel availability on demand for alternative-fuel vehicles, using data from a survey of some 600 potential car buyers in Germany. The survey was conducted as a computer-assisted personal interview and included a choice experiment involving cars with various fuel types. Applying a standard logit model, we show that fuel availability influences choices positively, but its marginal utility diminishes with supply. Furthermore, we derive consumers' marginal willingness to pay for an expanded service station network. The results suggest that a failure to expand the availability of alternative fuel stations represents a significant barrier to the widespread adoption of alternative-fuel vehicles.
Keywords: C25; D12; R41; 330; Alternative Fuels; Automobile; Fueling Infrastructure; Stated Preference; Kraftstoff; Regenerative Energie; Tankstelle; Infrastruktur; Konsumentenverhalten; Kraftfahrzeug; Umweltverträgliches Produkt; Deutschland